Hubungan Mekanisme Koping dengan Tingkat Kecemasan Pasien gagal Ginjal Kronik di Unit Hemodialisa RSUD Provinsi NTB - Istiana, Dian; Arifin, Zaenal; Megantari Putri, Heni Agustini; Syamdarniati, Syamdarniati; Nur Sukma Purqoti, Dewi (Jurnal Ilmiah STIKES Yarsi Mataram, 2021)
The Indonesian Society of Nephrology survey there are 18 million people in Indonesia suffering from chronic kidney disease. Chronic kidney disease is a progressive disorder of renal function and requires treatment in the form of kidney transplantation, peritoneal dialysis, hemodialysis and long-term outpatient treatment. Patients undergoing hemodialysis experience various problems arising from kidney malfunction. Anxiety is a psychological impact that hemodialysis patients often complain about. Coping mechanism is one of the factors that affect the patient's anxiety. This study aims to determine the relationship of coping mechanism with anxiety level in chronic renal failure patients in Hemodialisa Unit of NTB Provincial Hospital. This type of research is quantitative research with correlational research design using cross sectional approach. The selection of samples was conducted by purposive sampling method with a sample count of 69 respondents. The research instruments used HARS questionnaire, and Jalowiec Coping Scale questionnaire. Analyze the data in this study using Chi-Square test analysis. The results showed that there was a link between coping mechanisms and anxiety levels in chronic renal failure patients in the Hemodialysis Unit of NTB Provincial Hospital with a significance value of 0.009 (p<0.05). With the results of this study, it is expected that the family can provide support to patients to use adaptive coping so as to lower the level of anxiety of patients.